Outcome of twin-twin transfusion syndrome treated by laser therapy in Taiwan's single center: Role of Quintero staging system - Yao-Lung Chang; An-Shine Chao; Shuenn-Dyh Chang; Peter CC. Hsieh; Sheng-Yuan Su; Kuan-Ju Chen; Po-Jen Cheng; Tzu-Hao Wang (Elsevier, 2016)
Objective: To evaluate the outcome of twin-twin transfusion syndrome (TTTS) treated by fetoscopic laser therapy (FLT) stratified by Quintero staging. Materials and Methods: A total of 100 TTTS cases treated by FLT, from October 2005 to August 2014, were included in this study. Cases were divided into first and second half periods to evaluate the learning effect-related outcomes, and logistic regression was applied to determine the independent factors in predicting the perinatal outcomes. Results: The total fetal survival rate was 68.5%, two fetal survival rate was 55%, and at least one fetal survival rate was 82%. High Quintero stage (Stages III and IV) and small gestational age at delivery were two independent factors predicting lower two fetal survivals. Gestational age at delivery was the only independent factor predicting at least one survival. The odds ratios of high Quintero stage predicting lower two fetal survivals were 11.3 (p<0.001) and 4.8 (p=0.043) in the first and second periods, respectively. Conclusion: High Quintero stage and small gestational age at delivery were associated with low two survival rate in TTTS treated by FLT; after gaining experience with FLT, the effect of high Quintero stage on lower two survival rate would decrease.